ІНФОРМАЦІЙНА РОЗВІДКА ЯК СФЕРА ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ (International Journal of Innovative Technologies in Economy, 2018)
The paper presents information as a necessary condition for making an effective management decision, analyzes the main levels and technologies of information intelligence service as a professional activity, which involves the collection of information by relevant specialists in various forms as from the open as from closed sources, as well as its intellectual processing and delivery to the customer in a form suitable for him. Attention is drawn to the positioning of the intelligence service process in managerial counseling, staffing the features of strategic intelligence service information, business intelligence, competitive intelligence and immaterial intelligence. Primary and secondary sources for obtaining information and their value for the further formation of strategic approaches to management decisions are determined. The process of analysis of the data obtained indicates the feasibility of their assumptions, as well as the probability of future consequences. Equally important is the presentation of the findings, their interpretation, which will enable the customer to convince the need for certain managerial actions.